Theology and Women’s Agency in the Context of Intimate Partner Violence in Ghana - Elorm Ama Stiles-Ocran (African Journal of Gender and Religion (AJGR))
Intimate partner violence (IPV) is a growing problem in sub-Saharan Africa that limits women’s agency. Various studies have found that cultural norms and religion sustain women’s experiences of IPV, inspiring various theories among feminist scholars and within religion on women’s agency. This study determines whether and how theology contributes to the agency of IPV survivors. I draw upon constructivist grounded theory to inductively analyze the stories of thirteen abused Christian women in a mainline church in southern Ghana. My findings indicate that multiple systems, including informal social support networks, constrain survivors while simultaneously serving as conditions for their personal faith and individually constructed theologies. Indeed, these serve as catalysts to their self-enactments and emerging agency. These findings provide nuance to existing (and contested) conceptions of agency.